2000
DOI: 10.1002/(sici)1097-4628(20000523)76:8<1296::aid-app10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal crystallization kinetics of commercially important polyalkylene terephthalates

Abstract: The isothermal crystallization kinetics of virgin, melt‐mixed, and nucleated specimens of polyethylene terephthalate (PET), polypropylene terephthalate (PPT), and polybutylene terephthalate (PBT) were measured. The purpose of the study was to determine the difference in crystallization rate of PPT, which is to be commercially available in the near future, to the extensively studied, commercially important polyalkylene terephthalates PET and PBT. At equivalent supercooling, the crystallization rate of PPT was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Poly(butylene terephthalate) (PBT) is one of the high-volume usage commercial engineering plastics belonging to the aromatic polyester family with chemical functional groups similar to poly(ethylene terephthalate) (PET) and poly(trimethylene terephthalate) (PTT). Currently, PBT is widely used in many commercial applications due to its excellent properties such as high rate of crystallization, good moldability and fast mould cycle time, 1 good mechanical and thermal properties where the service temperature can be as high as 140 °C. Due to these beneficial properties, PBT becomes a promising blending component with other polymers to improve their original performance.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(butylene terephthalate) (PBT) is one of the high-volume usage commercial engineering plastics belonging to the aromatic polyester family with chemical functional groups similar to poly(ethylene terephthalate) (PET) and poly(trimethylene terephthalate) (PTT). Currently, PBT is widely used in many commercial applications due to its excellent properties such as high rate of crystallization, good moldability and fast mould cycle time, 1 good mechanical and thermal properties where the service temperature can be as high as 140 °C. Due to these beneficial properties, PBT becomes a promising blending component with other polymers to improve their original performance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, all the bicomponent fibers are partially crystalline for all draw ratios as a direct result of strain-induced crystallization of the molecular chains; some of this evidence is noted in Table 2 . A reason for the absence of cold crystallization for all the trials could be that the PBT helical structure restricts the melt to transform into an amorphous state upon cooling and instead prefers a crystalline state [ 1 ]. As a result, the degree of crystallinity is saturated and further drawing can only slightly affect the crystallite size [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polybutylene terephthalate (PBT), along with polyethylene terephthalate (PET), belongs to the widely commercialized family of polyalkylene terephthalate. Although both PBT and PET are semi-crystalline, the distinct molecular structures give rise to faster crystallization shown for PBT which has popularized it for injection molding where shorter cycle times are essential [ 1 ]. Both PBT and/or PET could be spun into continuous filaments then subsequently made into textiles; as such, mechanical properties of textiles that can withstand strains imposed by wearing are important, while other factors, such as comfort related to thermal and moisture management, should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that undercooling degree for the mold flux D is extremely small, [30] giving rise to the fact that the overall crystallization rate should be governed by the degree of undercooling relevant to free energy change for nucleation. [31][32][33][34][35][36] Accordingly, the formation of cuspidine phase for mold flux D is more dependent on undercooling degree compared with the case of mold flux B.…”
Section: A Isothermal Dsc Measurementmentioning
confidence: 97%
“…This result suggests that the overall crystallization rate should be retarded by the increase in the crystallization temperature, and the crystallization rate will be governed by nucleation rate as suggested by others for melt crystallization. [31][32][33][34][35][36]42] The effective crystallization rate constant k can be used to determine the crystallization activation energy through the Arrhenius equation. [42] 1 n ðln kÞ ¼ ln…”
Section: B Isothermal Melt Crystallization Kineticsmentioning
confidence: 99%